Exploring Financial Performance Disparities: An In-Depth Analysis of Companies Led by Foreign-Born CEOs Versus Non-Foreign-Born CEOs Within the S&P 500 - Salimi, Anwar Y.; Danesh, Ehsan (Journal of Accounting and Finance, 2024)
There is an increasing trend for companies to have foreign-born Chief Executive Officers. It was found that 101 companies in the S&P 500 had foreign-born CEOs. The purpose of this paper was to investigate whether companies with foreign-born CEOs exhibited better financial performance. The study adopted a quantitative approach. We gathered two datasets: one detailing the performance of companies with CEOs born in the United States, and the other delineating the performance of companies with CEOs born outside the United States. We utilized the T-test for the difference of means on these two sets of data. This statistical method allowed us to assess the variations in financial performance metrics between the two groups over a six-year period. The findings indicate that foreign CEOs consistently outperformed their domestic counterparts across all three studied KPI performance measures from 2018 to 2023. T-tests for the difference of means indicated that these results were statistically significant.